Robust hybrid mass damper. (4th August 2016) - Collette, C.; Chesné, S.
Abstract: In this paper, the design of a hybrid mass damper (HMD) is proposed for the reduction of the resonant vibration amplitude of a multiple degree-of-freedom structure. HMD includes both passive and active elements. Combining these elements the system is fail-safe and its performances are comparable to usual purely active systems. The control law is a revisited direct velocity feedback. Two zeros are added to the controller to interact with the poles of the plant. The developed control law presents the particularity to be simple and hyperstable . The proposed HMD is compared to other classical control approaches for similar purpose in term of vibration attenuation, power consumption and stroke.